Boundary vibration control of a floating wind turbine system with mooring lines. (August 2020) - He, Wei; Xiang, Weijie; He, Xiuyu; Li, Guang
Abstract: In this paper, we investigate dynamic modeling, active boundary control design, and stability analysis for a coupled floating wind turbine (FWT) system, which is connected with two flexible mooring lines. It is a coupled beam-strings structure, and we design two boundary controllers to restrain the vibrations of this flexible system caused by external disturbances based on the coupled partial differential equations and ordinary differential equations (PDEs–ODEs) model. Meanwhile, significant performance of designed boundary controllers and system's stability are theoretically analyzed, and a set of simulation results are provided to show efficacy of the proposed approach.